2017
DOI: 10.1016/j.nicl.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging in Parkinson's disease: Review and meta-analysis

Abstract: BackgroundNeuroimaging studies help us better understand the pathophysiology and symptoms of Parkinson's disease (PD). In several of these studies, diffusion tensor imaging (DTI) was used to investigate structural changes in cerebral tissue. Although data have been provided as regards to specific brain areas, a whole brain meta-analysis is still missing.MethodsWe compiled 39 studies in this meta-analysis: 14 used fractional anisotropy (FA), 1 used mean diffusivity (MD), and 24 used both indicators. These studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
190
6
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(240 citation statements)
references
References 124 publications
30
190
6
2
Order By: Relevance
“…As shown in Table 5, no significant differences were observed for any clinical characteristics and polyamine metabolite levels between PD patients and PD patients with DTI. 35 Spearman rank correlation test also revealed that mean FA values for significant clusters in PD patients correlated positively with DiAcSpd (r = 0.63, p = 0.003). 34 Accordingly, TBSS analysis detected a significant positive correlation between DiAcSpd and FA in an extensive white matter area in the brain of PD patients after normalization of LED and age (see Fig 2I, J; p < 0.05, familywise error-corrected; Peak Montreal Neurological Institute method x, y, z: 77, 90, 110; t max = 7.06; r max = 0.70; voxels = 45,836).…”
Section: Resultsmentioning
confidence: 84%
“…As shown in Table 5, no significant differences were observed for any clinical characteristics and polyamine metabolite levels between PD patients and PD patients with DTI. 35 Spearman rank correlation test also revealed that mean FA values for significant clusters in PD patients correlated positively with DiAcSpd (r = 0.63, p = 0.003). 34 Accordingly, TBSS analysis detected a significant positive correlation between DiAcSpd and FA in an extensive white matter area in the brain of PD patients after normalization of LED and age (see Fig 2I, J; p < 0.05, familywise error-corrected; Peak Montreal Neurological Institute method x, y, z: 77, 90, 110; t max = 7.06; r max = 0.70; voxels = 45,836).…”
Section: Resultsmentioning
confidence: 84%
“…Diffusion tensor imaging (DTI) is a powerful tool to investigate microstructural alterations to the human brain in vivo. In PD, this technique has been combined with voxel‐ or region‐of‐interest (ROI)‐wise (Atkinson‐Clement, Pinto, Eusebio, & Coulon, ; Schwarz et al, ), and graph‐theoretical analyses (Aarabi et al, ; Li et al, ; Nigro et al, ; Pereira et al, ). Tract‐based spatial statistics (TBSS) is a voxel‐wise method, specifically developed to minimize the methodological pitfalls caused by misalignment and misregistration in conventional voxel‐based analyses (Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…DTI in the SN was shown to be able to differentiate between PD at an early stage and healthy controls indicating that this neuroimaging technique may serve as a noninvasive early imaging marker for PD . Two recent meta‐analyses confirmed a notable effect size with lower fractional anisotropy (FA) in the SN of patients with PD . Microstructural changes on DTI may, however, also be seen in other brain regions depending on the underlying PD phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Two recent meta-analyses confirmed a notable effect size with lower fractional anisotropy (FA) in the SN of patients with PD. 21,22 Microstructural changes on DTI may, however, also be seen in other brain regions 22 depending on the underlying PD phenotype. Patients with freezing of gait, for example, display diffuse white matter abnormalities that involve several cortico-cortical, striato-frontal, and cerebello-pontine connections.…”
Section: Introductionmentioning
confidence: 99%